DEVELOPING AGILITY IN STUDENTS - Kholmirzayev Ernazar Jurayevich (Web of Journals Publishing, 2023)
This article highlights the role and importance of physical exercises aimed at mastering new movements in the development of agility in students.
Keywords: Movement qualities, sports games, coordination, muscle tone, jumping, technique.